Autoimmune-Mediated Thymic Atrophy Is Accelerated but Reversible in RelB-Deficient Mice - O’Sullivan, Brendan J.; Yekollu, Suman; Ruscher, Roland; Mehdi, Ahmed M.; Maradana, Muralidhara Rao; Chidgey, Ann P.; Thomas, Ranjeny (Frontiers in Immunology, 2018)
Polymorphisms impacting thymic function may decrease peripheral tolerance and hasten autoimmune disease. The NF-B transcription factor subunit, RelB, is essential for the development and differentiation of medullary thymic epithelial cells (mTECs): RelB-deficient mice have reduced thymic cellularity and markedly fewer mTECs, lacking AIRE. The precise mechanism of this mTEC reduction in the absence of RelB is unclear. To address this we studied mTECs and dendritic cells (DCs), which critically regulate negative selection, and thymic regulatory T-cells (tTreg) in RelB-/- mice, which have spontaneous multi-organ autoimmune disease. RelB-/- thymi were organized, with medullary structures containing AIRE- mTECs, DCs and CD4+ thymocytes, but fewer tTreg. Granulocytes infiltrated the RelB-/- thymic cortex, capsule and medulla, producing inflammatory thymic medullary atrophy, which could be treated by granulocyte depletion or RelB+ DC immunotherapy, with concomitant recovery of mTEC and tTreg numbers. These data indicate that central tolerance defects may be accelerated by autoimmune thymic inflammation where impaired RelB signaling impairs the medullary niche, and may be reversible by therapies enhancing peripheral Treg (pTreg) or suppressing inflammation.